The effect of laserpuncture shooting on the histomorphometry of the bursa of Fabricius in pullets (Gallus gallus) that lay eggs late - Tiarani, Ayu Kamila; Lokapirnasari, Widya Paramita; Soeharsono, Soeharsono (Jurnal Agro Veteriner, 2025)
The continuing increase in egg consumption has led to the need to ensure that the laying hen industry sector is able to keep up with the need for eggs, one way is by increasing the productivity of laying hens and ensuring that laying hens can lay eggs on time. This study aims to determine the number and diameter of the bursa of Fabricius lymphoid follicles in late-laying pullets laserpuncture. This research is a 2x4 factorial complete randomized design experimental study. Chickens were divided into two groups, First Grade and Second Grade. Each Grade group was further divided into four groups based on laserpuncture points, namely control, Ova, weigen, and Ova-weigen. The variables observed were the diameter and number of lymphoid follicles of the bursa of Fabricius microscopically. The observation data were analyzed statistically using analysis of variance (ANOVA) followed by the Duncan test. The results of the analysis showed that 0.5 Joule laserpuncture had a significant effect on the diameter and number of the bursa of Fabricius lymphoid follicles (p<0.05). Laserpuncture shooting 0.5 Joules at the Wei Gen point shows the smallest diameter of the lymphoid follicles. While Ova point showed the smallest number of bursa Fabricius lymphoid follicles.